Pengaruh Struktur Modal, Profitabilitas Dan Pertumbuhan Perusahaan Terhadap Nilai Perusahaan Dengan Kebijakan Dividen Sebagai Variabel Intervening Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2018-2022 - Syavira Adinda; Desi Ika; Rizki Fillhayati Rambe (Jurnal Ekonomi Bisnis, Manajemen dan Akuntansi (Jebma), 2024)
This study aims to determine the effect of capital structure, profitability, and company growth on the company's value with dividend policy as an intervening variable in manufacturing companies listed on the Indonesia Stock Exchange. The type of approach in this study is associative quantitative with data collection using documentation studies and secondary data in the form of annual reports published by the company on the official website of the IDX, www.idx.co.id. The study population is all manufacturing companies in Indonesia Stock Exchange. Sampling technique with purposive sampling obtained samples of 35 companies with observation years starting from 2018-2022 (5 years) so that 175 samples were obtained. Data analysis techniques used in this study using path analysis with SPSS v.26. The results of this study indicate that the capital structure, profitability, and growth of the company have a significant effect on dividend policy. The capital structure, profitability, growth of the company significantly affect the value of the company, while the dividend policy does not affect the value of the company. Dividend policy cannot mediate the influence of the company's capital structure, profitability and growth on the value of the company in manufacturing companies listed on the Indonesia Stock Exchange in 2018-2022.